Bone Mineral Status in Children and Adolescents with Klinefelter Syndrome. (16th June 2016) - Stagi, Stefano; Di Tommaso, Mariarosaria; Manoni, Cristina; Scalini, Perla; Chiarelli, Francesco; Verrotti, Alberto; Lapi, Elisabetta; Giglio, Sabrina; Dosa, Laura; de Martino, Maurizio
Abstract : Objective . Klinefelter syndrome (KS) has long-term consequences on bone health. However, studies regarding bone status and metabolism during childhood and adolescence are very rare. Patients . This cross-sectional study involved 40 (mean age: 13.7 ± 3.8 years) KS children and adolescents and 80 age-matched healthy subjects. For both patient and control groups, we evaluated serum levels of ionised and total calcium, phosphate, total testosterone, luteinising hormone, follicle stimulating hormone, parathyroid hormone (PTH), 25-hydroxyvitamin D (25(OH)D), 1, 25-dihydroxyvitamin D, osteocalcin, bone alkaline phosphatase, and urinary deoxypyridinoline concentrations. We also calculated the z -scores of the phalangeal amplitude-dependent speed of sound (AD-SoS) and the bone transmission time (BTT). Results . KS children and adolescents showed significantly reduced AD-SoS (p < 0.005 ) and BTT (p < 0.0005 ) z -scores compared to the controls. However, KS patients presented significantly higher PTH (p < 0.0001 ) and significantly lower 25(OH)D (p < 0.0001 ), osteocalcin (p < 0.05 ), and bone alkaline phosphatase levels (p < 0.005 ). Interestingly, these metabolic bone disorders were already present in the prepubertal subjects. Conclusions . KS children and adolescents exhibited impaired bone mineral status and metabolism with higher PTH levels and a significant reduction of 25-OH-D and bone formation markers. Interestingly, this impairment was already evident in prepubertal KS patients. Follow-ups should be scheduled with KS patients to investigate and ameliorate bone mineral status and metabolism until the prepubertal ages.